2020
DOI: 10.1039/d0tc03309j
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating charge transport mechanisms in cellulose-stabilized graphene inks

Abstract: Solution-processed graphene inks that use ethyl cellulose as a polymer stabilizer are blade-coated into large-area thin films. Following blade-coating, the graphene thin films are cured to pyrolyze the cellulosic polymer,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…38 Therefore, the position of the G-peak at ∼1580 cm −1 demonstrates a film composed of few-layered graphene flakes, further substantiated with the characteristic I G /I 2D ratio of ∼1.96, close to that of mechanically exfoliated few-layer graphene. 39 The analysis of a population of 50−100 graphene flakes by AFM revealed the presence of graphene nanosheets with a mean lateral size of 97.89 ± 4.07 nm and mean thickness of 1.59 ± 0.12 nm, dimensions consistent with previous reports of EC-stabilized graphene 31,40 and shearmixed graphene nanosheets (Figure 1c,d). 41 While EC provides a suitable dispersant for the production of graphene, nitrocellulose (NC) has previously been demonstrated as an alternative dispersant yielding superior mechanical properties.…”
Section: ■ Results and Discussionsupporting
confidence: 89%
“…38 Therefore, the position of the G-peak at ∼1580 cm −1 demonstrates a film composed of few-layered graphene flakes, further substantiated with the characteristic I G /I 2D ratio of ∼1.96, close to that of mechanically exfoliated few-layer graphene. 39 The analysis of a population of 50−100 graphene flakes by AFM revealed the presence of graphene nanosheets with a mean lateral size of 97.89 ± 4.07 nm and mean thickness of 1.59 ± 0.12 nm, dimensions consistent with previous reports of EC-stabilized graphene 31,40 and shearmixed graphene nanosheets (Figure 1c,d). 41 While EC provides a suitable dispersant for the production of graphene, nitrocellulose (NC) has previously been demonstrated as an alternative dispersant yielding superior mechanical properties.…”
Section: ■ Results and Discussionsupporting
confidence: 89%
“…Following synthesis, the NMC particles were uniformly coated with graphene and ethyl cellulose (GrEC) using a previously established solution-phase method. , The coating conformality was confirmed using SEM and transmission electron microscopy (TEM) (Figure a–c), which revealed the presence of a percolating network of graphene flakes throughout the electrode, consistent with prior work. ,, After fabricating electrodes with the GrEC powder (NMC-GrEC), the electrode was heated to pyrolyze the ethyl cellulose (EC) polymer, which largely volatilizes the EC, compacts the electrode, and generates a carbon residue that helps form a percolating, electrically conductive network among the graphene-coated NMC particles. ,, Subsequent Raman spectroscopy of the electrode confirmed that the ratio of the D and G peaks decreased (at 1350 and 1580 cm –1 , respectively) (Figure S3), suggesting that EC decomposition resulted in a more graphitic carbon network that facilitates efficient charge transfer. The uncoated NMC powder was also mixed with carbon black (CB) and polyvinylidene fluoride (PVDF) to fabricate control electrodes (NMC-CBPVDF).…”
Section: Resultssupporting
confidence: 61%
“…The I D / I G ratio of CEG was increased from 0.11 to 0.19, revealing a low defect density and a high degree of sp 2 carbon . The existence of cellulose with sp 3 carbon induced the increment in I D / I G ratio, but did not destroy the sp 2 carbon structure of graphene Figure b,c shows Lorentzian fitting lines of 2D peaks of graphite and CEG.…”
Section: Resultsmentioning
confidence: 96%
“…26 The existence of cellulose with sp 3 carbon induced the increment in I D /I G ratio, but did not destroy the sp 2 carbon structure of graphene. 27 Figure 2b,c shows Lorentzian fitting lines of 2D peaks of graphite and CEG. After exfoliation, the intensity of the 2D band at the fwhm decreased from 79.12 to 53.99, which revealed that the number of graphene layers decrease from more than 10 layers of graphite to 2−4 layers of CEG.…”
Section: Preparation and Characterization Of Ceg Inkmentioning
confidence: 99%